Study of tribotechnical characteristics of composite coatings formed by the method of electrospark alloying - Mikosianchyk, O.; Shamrai, V.; Lopata, L.; Mnatsakanov, R.; Nosko, P.; Semak, I. (Problems of Tribology, 2026)
The results of studying the tribotechnical characteristics of composite coatings formed by the electric spark alloying (ESA) method are presented. It has been established that the key factor in controlling the stress-strain state of the “coating-base” system is the optimization of the thickness and continuity of the strengthened layer. Using the finite element method, it was demonstrated that for coatings with a thickness of 100 μm, the minimum stress concentration is achieved when the coating continuity is within 60–80%. Deviations from these values (less than 50% or greater than 80%) lead to an increase in local stresses. Modeling showed that the maximum equivalent stresses are localized at depths up to 30 μm for BK8 coatings and up to 50 μm for KHN25 coatings (with a total layer thickness of 120 μm), which reduces the stress–strain state of the substrate under external loading. Experimental abrasive wear tests in an environment with loosely fixed abrasive particles showed that the minimum weight loss is achieved when the coating continuity is 55–75%, with an optimal value of 70% and a ratio of strengthened to unstrengthened areas of 2:1. Comparative analysis of materials revealed that coatings made of WC-8Co alloy (microhardness 10000 MPa) exhibit 1.8–2 times higher weight wear compared with KHN25 alloy (microhardness 8500 MPa). The obtained results make it possible to scientifically justify the selection of ESA modes and electrode material compositions for the restoration of machine parts operating under conditions of intensive abrasive action